Square difference labeling of some union and disjoint union graphs - Sherman, Z. (Algebra and Discrete Mathematics, 2018)
The paper deals with methods of constructing square difference labeling of caterpillars and graphs derived from two operations: path union of cycles and disjoint union of stars. The existence of the square difference labeling of disjoint union of any SD graph with path is proved.